Acute Rheumatic Fever (ARF) in a patient of Chronic Mucocutaneous Syndrome or Mucocutaneous Candidiasis having Diarrhea and Skin Rash - Furqan ul Haq, Muqsit Ali Shaukat, Hamza Yunus, Sahibzada Muhammad Qasim, Tanveer Hamid, Ihtisham Qayum, Syed Sadam Hussain, Sohail Ahmad, Asad Riaz, Qazi Muhammad Farooq Wahab, (Pakistan Journal of Medical & Health Sciences, 2023)
Acute Rheumatic fever (ARF) is the most common cause of acquired heart disease in the developing world. It is an immunological reaction to group A beta-hemolytic streptococcus Pyogenes. It occurs 2-4 weeks after group A streptococcal pharyngitis due to the development of antistreptococcal antibodies that cross-react with antigens in various tissues of the body, especially cardiac and basal ganglia neuronal antigens. Clinical features of acute rheumatic fever include fever, joint pain, myocarditis, nodules in subcutaneous tissue, Erythema Marginatum, and chorea. Patients with immunodeficiency like mucocutaneous candidiasis are especially prone to recurrent mucocutaneous infections (tonsillopharyngitis, thrush, skin abscess), which can predispose to acute rheumatic fever and subsequent development of rheumatic heart disease over the years. Keywords: Acute rheumatic fever, chronic mucocutaneous syndrome, skin rash,